2021
DOI: 10.1007/s10514-021-09990-9
|View full text |Cite
|
Sign up to set email alerts
|

How to train your differentiable filter

Abstract: In many robotic applications, it is crucial to maintain a belief about the state of a system, which serves as input for planning and decision making and provides feedback during task execution. Bayesian Filtering algorithms address this state estimation problem, but they require models of process dynamics and sensory observations and the respective noise characteristics of these models. Recently, multiple works have demonstrated that these models can be learned by end-to-end training through differentiable ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 16 publications
(37 reference statements)
0
41
0
Order By: Relevance
“…This is particularly true for some of the richest, most information-dense sensing modalities, such as images, audio, or tactile feedback, as well as in interaction-rich applications that need to reason about difficult-to-model contact dynamics. These systems also tend to have more complex, heteroscedastic (variable) noise profiles [6]. For example, an object position estimate from an image might rapidly switch from being extremely precise under nominal operating conditions to completely useless under occlusion or poor lighting.…”
Section: Stanfordmentioning
confidence: 99%
See 3 more Smart Citations
“…This is particularly true for some of the richest, most information-dense sensing modalities, such as images, audio, or tactile feedback, as well as in interaction-rich applications that need to reason about difficult-to-model contact dynamics. These systems also tend to have more complex, heteroscedastic (variable) noise profiles [6]. For example, an object position estimate from an image might rapidly switch from being extremely precise under nominal operating conditions to completely useless under occlusion or poor lighting.…”
Section: Stanfordmentioning
confidence: 99%
“…To retain the benefits of a probabilistic state estimator while circumventing the need for analytical models, a recent line of work has shown that we can treat Bayesian filters as a differentiable component of a computation graph [6][7][8][9][10]. These differentiable filters allow end-to-end estimation errors to be backpropagated directly through the structure of the estimator itself, enabling data-driven learning for system models and uncertainties that are optimized for a specific state estimation setting.…”
Section: Stanfordmentioning
confidence: 99%
See 2 more Smart Citations
“…In [25], they utilise conditional normalisation flows to construct flexible probability distributions for differentiable particle filters. A comparison of differentiable filters can be seen in [26]. The approach described in this paper differs from this body of previous work since we focus on ensuring resampling is differentiable without having to change how resampling operates.…”
Section: Introductionmentioning
confidence: 99%